American afterlife : a novel - Hoffmeister, Pedro (Crooked Lane, 2022)
"The Pacific Northwest lies in ruins in the aftermath of the 9.2 Cascadia earthquake. There is a tsunami at the coast, annihilated infrastructure in all the towns and cities, and failed dams in the Oregon river valley where 15-year-old Cielo lives with her mother, a fearful evangelical who's become caught up in a fearsome cult called The Collection of Redeemed Souls. Cielo and her mother, Mexican citizens without U.S. papers, have always had their status teeter on the edge--and now it's about to plunge into the abyss. When the earthquake hits, Cielo's mother hasn't been home in days, but Cielo suspects that she's holed up with the cult and might even be dead. When the National Guard arrives to evacuate survivors, she stays behind in the flooded city to find her body. Members of The Collection of Redeemed Souls have also chosen to stay, and their disciples are capturing anyone still left behind and converting them to the cult by force. Entering a deadly game of cat-and-mouse, Cielo tries to evade the cult at every turn as she desperately searches for her mother's remains. With gunfights and mass killings engulfing the city, Cielo is one step away from her own demise, but the bonds of blood drive her on toward a confrontation with pure evil--and a final chance for her mother's redemption"--